Analysis of Nurse Perception Factors on Compliance Implementing Patient Safety Standards in Emergency Installations and Intensive Care Unit - Safrullah, Safrullah; Bashir , Asri (Rifa'Institute, 2022)
Background: Patient safety standards are a global issue and a top priority for hospital health services. Every health service needs to strive for patient safety Various previous studies on the application of patient safety standards have been carried out only explaining external factors such as education, training, infrastructure and leadership with apassion for compliance behavior in the application of patient safety standards, while internal factor sare still very few, in this study what will be studied is internal factors in nurses, one of the internal factors that cannot be explained is the perception factor. Objective: The purpose of this study is to Analysis of Nurse Perception Factors on Compliance Implementing Patient Safety Standards in Emergency Installations and Intensive Care Units Tgk Abdullah Syafi' Hospital. Method: The type of research used is quantitative correlative with a cross sectional design. This research was conducted at Tgk Abdullah Syafi'i Hospital. The subjects in this study were all nurses working in the emergency room (ER) and the intensive care unit (ICU) as many as 63 people. The instrument used in this study was a questionnaire consisting of independent variables and a dependent variable questionnaire. Result and Discussion: The most dominant factor influencing the application of patient application standards is the action cue with an OR value of 4,702. this means that the higher the actioncue, the better the implementation of patient safety standards by 4,702 times compared to the action cues that low. Value B = natural logarithm of 4.702 = 1.584 because the value of B is positive, the action cue has a positive relationship with the application of patient safety standards. Conclusions: There is an influence between perceptions of benefits, perceptions of obstacles and cues for action on the application of patient safety standards